SOCIAL WORK WITH HIV-POSITIVE CLIENTS AND THEIR SEXUAL PARTNERS - KOLOMIYETS, Olena (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
The theoretical and practical regulations concerning social work with HIV-positive clients and their sexual partners are analyzed. The main problems of discordant couples, including an analysis of the main obstacles for the social support of this category of social work clients are highlighted. The basic principles of providing social assistance to HIV-positive clients and their sexual partners are determined. The specific steps of the social work algorithm with HIV-positive clients and their sexual partners are identified. The attention is focused on correcting the partners behaviors taking into account the possibilities of mutual support.